BULK FLOTATION OF GALENA-SPHALERITE COMPLEX ORE USING ALICYCLOBACILLUS FERROOXYDANS SKC/SAA-2 BACTERIA - PAMUNGKAS (NIM : 12513026), TRIMOKO
Lead and zinc are two metals which have many benefits in life. The main minerals producing both metals are galena (PbS) and sphalerite (ZnS). Prior to the extraction process, both galena and sphalerite must be through concentration process. The concentration process of sulfide minerals that have been proven and widely done is flotation. Flotation is a process of separating valuable minerals from its impurities by floating one or several minerals assisted by chemical reagents. In this modern era, the issue of environmental hazards is becoming a focus of people attention. Flotation process with chemicals reagents has a negative impact to the environment because it is difficult to be decomposed when disposed to environment. Recently, there’s a breakthrough development for environmentally friendly flotation process by replacing chemical reagents with bacteria or commonly called bioflotation. Bioflotation process is able to reduce environmental pollution because bacteria is an organic material that is easy to be decomposed, and it can reduce the operating cost of the flotation process. In this experiment, mineral interactions with Alicyclobacillus ferrooxidans SKC/SAA-2 bacteria and bioflotation process with variation of pH, bacterial concentration, and conditioning time will be observed. The experiment was initiated by interacting Alicyclobacillus ferrooxidans SKC/SAA-2 bacteria with galena concentrate, sphalerite concentrate, and pure silica minerals with pH variation to see the transformation in mineral surface properties using contact angle analysis, FTIR, and SEM-EDS. Then the bioflotation process was performed on galena-sphalerite complex ore which has a silica-based main impurities with variation of pH, bacterial concentration, and conditioning time. The results of minerals interaction with Alicyclobacillus ferrooxidans SKC/SAA2 bacteria showed that the bacteria were able to change the surface properties of galena minerals and sphalerite minerals to hydrophobic, as indicated by the analysis of contact angles which gave contact angle on galena mineral 118.1o and sphalerite mineral 69.88°. In pure silica minerals, the mineral surface properties do not change which remain hydrophilic. As well as FTIR analysis, the mineral surface properties of galena and sphalerite become hydrophobic and pure silica minerals remain hydrophilic. In bulk bioflotation experiments to float galena and sphalerite minerals, the most optimum conditions were obtained at pH 3, using 20% v/v bacterial concentration, and with 60 minutes of conditioning time which capable of producing the largest galena recovery of 90.21% and recovery of sphalerite 86.83%. The grade of Pb element increasing from 3.46% to 4.82%, while Zn element increasing from 6.65% to 8.91%.